Recent applications of chloroaluminate ionic liquids in promoting organic reactions - Kumar, Anil; Sarma, Diganta (Symposium on Ionic Liquids - Fundamentals, Progress, Challenges and Opportunities held at the 226th American-Chemical-Society National Meeting, 2005)
Chloroaluminate ionic liquids composed of AICl(3) and organic cations can promote a variety of organic reactions. The composition of these chloroaluminate ionic liquids governs the acidity and basicity of solvent media, in which the reactions are carried out. Useful physico-chemical properties of these ionic liquids and the recent work on their role in accelerating organic reactions are described in the present article.

Rare earth metal triflates promoted diels-alder reactions in ionic liquids - Sarma, Diganta; Kumar, Anil (Applied Catalysis A-General, 2008)
Rare earth metal triflates, when used with ionic liquids can promote Diels-Alder reactions carried out with different dienes and dienophiles suggesting an enhancement in the catalytic power of the triflates in ionic liquids. It is possible to recover and reuse the ionic liquid phase with triflates to give comparable yields and stereoselectivities even after six cycles. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Diels-Alder reactions; ionic liquids; rare earth metal triflates